THE INFLUENCE OF VIRAL MARKETING AND PRICE DISCOUNTS THROUGH SOCIAL MEDIA INSTAGRAM TO PURCHASE DECISION ON MARKETPLACE SHOPEE - Teguh Maulana; Gugyh Susandy (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2019)
The rapidly evolving communications, media and informatics technologies and the widespread development of the global information infrastructure have influenced the ways and patterns of business activities in the trade, social and political governance industries. One of the technologies used by people, organizations and companies is the internet. With the growing use of the internet in Indonesia is a potential for business people in Indonesia, where as increasing internet users then this will also encourage the growth of e-commerce in Indonesia. E-commerce activities in Indonesia penetrate various activities from small-scale industry to large industries. Small-scale e-commerce activities are now developing all over Indonesia, because of the availability of various way of kind to transaction online with ease. Such as marketplace which is a combination of several online stores that sell in one place.The purpose of this research is to know the influence of Viral Marketing and Discount Price through social media instagram of Purchase Decision on Shope marketplace. The research method used is descriptive method and explanatory survey. The sample selection was done by using purposive sampling technique with the number of samples of 100 respondents. The data used is interval data. Statistical method for data test using SPSS 22 for windows program. By using multiple linear regression analysis obtained equation Y = 16.632 + 0,274X1 + 0,219 X2 + e. From the results of the research note that Viral Marketing partially influence on the Purchase Decision but not for Discounts price, and Viral Marketing and Price discounts simultaneously affect the Purchase Decision.